2020
DOI: 10.1038/s41467-020-15305-w
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive tract extracellular vesicles are sufficient to transmit intergenerational stress and program neurodevelopment

Abstract: Extracellular vesicles (EVs) are a unique mode of intercellular communication capable of incredible specificity in transmitting signals involved in cellular function, including germ cell maturation. Spermatogenesis occurs in the testes, behind a protective barrier to ensure safeguarding of germline DNA from environmental insults. Following DNA compaction, further sperm maturation occurs in the epididymis. Here, we report reproductive tract EVs transmit information regarding stress in the paternal environment t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
179
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 157 publications
(215 citation statements)
references
References 85 publications
(80 reference statements)
5
179
0
4
Order By: Relevance
“…Future studies could incorporate a post-treatment recovery period aligned to the mouse spermatogenic cycle (~ 42 days) before mating for the F1 generation. A www.nature.com/scientificreports/ very recent study reported that effects of 28 days of paternal chronic stress had intergenerational effects after 12 weeks of post-stress recovery but not after 1 week 30 . That extended period exceeds several spermatogenic cycles, and when allowing for the elimination of mature epididymal sperm, it suggests that a life-long imprint of that history of paternal stress is likely to originate from testicular germ cells through more stable epigenetic modifications, such as DNA methylation or other alterations in various somatic cells that maintain differences in non-coding RNAs in germ cells.…”
Section: Discussionmentioning
confidence: 99%
“…Future studies could incorporate a post-treatment recovery period aligned to the mouse spermatogenic cycle (~ 42 days) before mating for the F1 generation. A www.nature.com/scientificreports/ very recent study reported that effects of 28 days of paternal chronic stress had intergenerational effects after 12 weeks of post-stress recovery but not after 1 week 30 . That extended period exceeds several spermatogenic cycles, and when allowing for the elimination of mature epididymal sperm, it suggests that a life-long imprint of that history of paternal stress is likely to originate from testicular germ cells through more stable epigenetic modifications, such as DNA methylation or other alterations in various somatic cells that maintain differences in non-coding RNAs in germ cells.…”
Section: Discussionmentioning
confidence: 99%
“…In mammals, different exosomes, such as epididymosomes, are important actors in sperm maturation through their constant exchanges with epididymal sperm [82]. They also have an action on the transfer to the progeny of epigenetic traits [82,83]. In birds, many protein components expected to make part of seminal exosomes were reported to be present in the seminal plasma of the domestic chicken [14,19,23] and of one of the chicken ancestors, the red jungle fowl [14].…”
Section: Exosomal Proteins and Sperm Maturationmentioning
confidence: 99%
“…También se han encontrado cambios en el grado de metilación de las histonas H3 y H4 asociado con restricción calórica y trastornos de aprendizaje [1][2][3] ; y en el contenido de miARN en oocitos y espermatozoides. Estos miRNA regulan la modificaciones post-traduccionales de las histonas y afectan el neurodesarrollo fetal 5,6 . Al respecto, recientemente Chan y cols.…”
Section: The Inheritance Of Covid-19 Pandemicunclassified
“…En este estudio, los miARNs encontrados en los exosomas de las células epiteliales epididimales de animales estresados afectaron genes relacionados con señales sinápticas y transporte de neurotransmisores en el sistema nervioso central del feto. Estudios complementarios realizados in vitro en el mismo trabajo permitieron determinar que corticosterona 1,4 μM pudo replicar el efecto del estrés en el perfil de miARN de las células epiteliales epididimales, y que los espermatozoides aislados de sujetos estresados (6 meses de puntuación alta en examen de percepción de estrés) presentaron un perfil de miARN diferente al de los sujetos normales, revelando que los miARN constituyen otro factor epigenético posiblemente responsable de la herencia transgeneracional masculina en caso de estrés 5 .…”
Section: The Inheritance Of Covid-19 Pandemicunclassified